A practical guide to fetal echocardiography : normal and abnormal hearts - Abuhamad, Alfred; Chaoui, Rabih (Philadelphia, PA : Wolters Kluwer, 2022)
Covering every aspect of fetal heart examination and all major cardiac malformations, A Practical Guide to Fetal Echocardiography is widely acknowledged as the definitive text in this challenging field. This award-winning title clearly depicts examples of commonly seen abnormalities and day-to-day cases, as well as rare pathology. Authored by renowned experts, the fully updated fourth edition is a lavishly illustrated, easy-to-read text designed to serve as a comprehensive reference for all practitioners involved in cardiac imaging. Images are accompanied by clear, colorful schematic drawings that depict cardiac abnormalities. Features the addition of Approach to Diagnosis, an algorithm at the end of each chapter to assist providers in reaching the proper diagnosis. Includes numerous tables that outline common and differentiating features of various cardiac malformations. Covers the technical aspects of the cardiac exam in the first half of the text; the second half features detailed discussions of fetal cardiac malformations, each presented in a practical, methodical format that includes the definition, spectrum of disease and incidence, the use of gray scale, color Doppler, 3D and early gestation ultrasound in diagnosis, followed by the differential diagnosis, prognosis, and outcome. Features a practical, concise, easy-to-use format, making it indispensable for both physicians and sonographers in the detection of congenital heart disease.
Bibliogr. odkazy
Register
Keywords: echokardiografia -- metódy; srdce fetálne -- anatómia a histológia -- fyziológia -- abnormality; formovanie tela (embryológia); chyby srdcové vrodené; ilustrácie lekárske; príručka